Fertility preservation in chemo-radiotherapy for rectal cancer: A combined approach. (November 2019) - Mariani, S.; Chiloiro, G.; Villa, P.; Meldolesi, E.; Barbaro, B.; Di Giorgio, A.; Corrado, G.; Corvari, B.; Giraffa, M.; Scambia, G.; Valentini, V.; Gambacorta, M.A.
Highlights: Young females affected by rectal cancer need counselling on fertility preservation. Ovarian transposition and cryopreservation are feasible. Advances in radiation therapy techniques can help reducing fertility impairment. A multidisciplinar approach is recommended. Abstract: Introduction: Colorectal cancer is a very common form of cancer worldwide, affecting an increasing number of young women. Standard treatment for locally advanced rectal cancer (LARC) can pose a threat to fertility in these patients. Case presentation: We present the case of a young woman affected by LARC who expressed a desire for child-bearing. The treatment she was proposed, according to guidelines, was neoadjuvant chemo-radiotherapy (CRT) followed by delayed surgery, carrying with it a high risk for amenorrhea. Counselling was performed before the initiation of treatment, with the aim of preserving fertility by the proposal of GnRH agonist administration, ovarian transposition and ovarian tissue cryopreservation, which the patient accepted. Treatment was then successfully completed. The patient presented regular menstrual period from before the surgery. Discussion: Ovarian tissue is very sensitive to radiations. Transposition of the organ can prevent ovarian insufficiency by placing it outside the radiation field, while ovarian tissue cryopreservation and orthotopic transplantation offers the possibility to restore fertility in the case of organ failure. We performed both of the techniques. GnRH analogs administration allowed to diminish the risk of ovarian cytotoxicity. Radiation treatment plan was optimized in order to minimize the dose to organs at risk (ovary and vagina in particular); position of the uterus, which is quite radiosensitive too, was monitored with daily cone-beam CT (CBCT). Conclusion: The strategy proposed seemed safe and effective, resulting in radical treatment and persistence of regular menstrual period. Further studies are needed.